Characterization of Domain Deletion and/or Duplication Mutants of a Recombinant Chimera of Tissue-Type Plasminogen Activator and Urokinase-Type Plasminogen Activator (rt-PA/u-PAI) - Nelles, L; Lijnen, H R; Van Nuffelen, A; Demarsin, E; Collen, D (Thrombosis and Haemostasis, 1990)
Chimeric molecules comprising the A-chain of tissue-type plasminogen activator (t-PA) and the catalytic domain of urokinase-type plasminogen activator (u-PA) have intact enzymatic characteristics of u-PA, but only partial fibrin-binding properties of t-PA (Nelles et al., J Biol Chem 1987; 262: 10855–62). The following domain deletion and/or duplication mutants of such a t-PA/u-PA chimera were constructed, purified and charactertzed: rt-PA-ΔFE∇/u-PA, with deletion of the finger-like (F) and epidermal growth factor-like (E) domains, rt-PA-ΔK1∇K2/u-PA, with kringle 1 (K1) replaced by a second copy of kringle 2 (K2), and rt-PA-ΔFEK1∇K2/u-PA, with F and E domain deletions in rt-PAΔK1∇K2/u-PA.The specific activities on fibrin plates of the single-chain (sc) chimeras ranged between 68,000 IU/mg for rt-PA-ΔK1∇K2/scu-PA and 200,000 IU/mg for rt-PA-ΔFEK1∇K2/scu-PA, as compared to L20,000 IU/mg for rscu-PA. The specific activities of their plasmin-generated two-chain (tc) derivatives ranged between 120,000 IU/mg for rt-PA-ΔK1∇K2/tcu-PA and 240,000 IU/mg for rt-PA-ΔFEK1∇K2/tcu-PA, as compared to 100,000 IU/mg for rtcu-PA. All two-chain chimeras activated plasminogen following Michaelis-Menten kinetics, with catalytic efficiencies between 0.072 μM−1s−1 for rt-PA-ΔK1∇K2/tcu-pA and 0.081 pM−1 s−1 for rt-PA-ΔFEK1∇K2/tcu-PA, as compared to 0.088 μM−1 s−1 for rtcu-PA. CNBr-digested fibrinogen enhanced the initial rate of plasminogen activation by a factor 2.2 to 6.2, as compared to 4.9 for rtcu-PA. The fibrin-affinity of the chimeras decreased in the order rt-PA > rt-PA-ΔK1∇K2/u-PA > u-PA and that for lysine in the order rt-PA-ΔFEK1∇K2/u-PA > > t-PA/u-PA ⩽ st-PA > rt-PA-ΔFE/u-PA > u-PA. All single-chain plasminogen activators caused a time and concentration-dependent clot lysis in an in vitro plasma clot lysis system, with equi-effective doses (causin g 50% clot lysis in 2 h) ranging between 0.53 and 0.90 μg/ml, as compared to 1 .7 μg/ml for rscu-PA, and were associated with comparable residual fibrinogen levels of approximately 80%.Thus, substitution of K1 by a second copy of K2 in the chimeric protein t-PA/u-PA enhances the affinity for both fibrin and lysine significantly and improves the fibrinolytic potency in an in vitro clot lysis system marginally.